Foreignization and domestication of Indonesian cultural words in the english translation of pramoedya ananta toer's jejak langkah - Rosydatul Faizzah (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2018)
wt,1.,/ws.c.1